Radical Scavenging Activity and Acute Toxicity of Bitter Melon (Momordica Charantia L.) Seed Oil - Lina Winarti; Lusia Oktora Ruma Kumalasari; Evi Umayah Ulfa (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Bitter Gourd or bitter melon (Momordica Charantia L.) is a common type of vegetable and safe for daily consumption. The seeds are part of bitter gourd that useless. Research on bitter melon seed oil has promising commercial applications. This study aims to determine the antioxidant potential and safety of bitter melon seed oil through acute toxicity study. The content of phenols, flavonoids, and antioxidant activity was analyzed. The antioxidant activity was evaluated using the DPPH method. Antioxidant activity is expressed as an IC-50 value. The results showed that the phenol content of bitter melon seed oil was 0.0118 ±0.0006%, the flavonoid content was 0.0127±0.0004%. From the antioxidant activity study, the IC-50 of vitamin C was 2.41 μg / ml, while an IC-50 of bitter melon seed oil was 11.31 ± 0.77 mg/ml. The results of this antioxidant activity study showed very weak activity. The results of the acute-toxicity study show LD-50 cannot be determined precisely because up to the highest dose of 100 ml/kg does not cause death even though it causes toxic symptoms such as diarrhea. Overall, test results indicate that bitter melon seed oil is a compound that is categorized as practically non-toxic with low antioxidant activity.